2013
DOI: 10.3109/00365521.2013.867361
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 22-gauge aspiration needle with 22-gauge biopsy needle in endoscopic ultrasonography-guided subepithelial tumor sampling

Abstract: OBJECTIVE. Endoscopic ultrasonography (EUS)-guided fine-needle aspiration (EUS-FNA) may facilitate tissue sampling for histopathological diagnosis of subepithelial tumors (SETs) in the gastrointestinal (GI) tract. However, immunohistochemistry is not always feasible using EUS-FNA samples due to the low quality of specimens often obtained by aspiration. This study aimed to compare the use of 22-gauge (G) EUS-guided fine-needle biopsy (EUS-FNB) with 22G EUS-FNA for core sampling used for histopathological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
124
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 29 publications
3
124
0
1
Order By: Relevance
“…Patients who were randomized to EUS-FNB had significantly higher diagnostic yield compared to patients who underwent EUS-FNA (75 % vs. 20 %, P = 0.010) [28]. Previously published prospective studies have also noted high diagnostic accuracy of the FNB technique in non-pancreatic mass lesions [23,35]. A recent study evaluated 125 patients with nonpancreatic masses using the 22-G core biopsy needle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who were randomized to EUS-FNB had significantly higher diagnostic yield compared to patients who underwent EUS-FNA (75 % vs. 20 %, P = 0.010) [28]. Previously published prospective studies have also noted high diagnostic accuracy of the FNB technique in non-pancreatic mass lesions [23,35]. A recent study evaluated 125 patients with nonpancreatic masses using the 22-G core biopsy needle.…”
Section: Discussionmentioning
confidence: 99%
“…Data are limited from randomized controlled trials comparing EUS-FNA to EUS-FNB in non-pancreatic mass lesions. [35,36] The published diagnostic yield of EUS-FNA for gastric subepithelial masses ranges from 42 % to 92 % [37,38]. Recently, Kim et al conducted a randomized controlled trial of 22 patients with gastric subepithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the lower diagnostic accuracy may be related to the need for histology to facilitate immunohistochemical staining or cellular architecture to solidify a final diagnosis. EUS with fine needle biopsy (FNB) has been recently shown to have a high diagnostic accuracy in these lesions 7,8…”
Section: Introductionmentioning
confidence: 99%
“…However, in one study using a new EUS histology needle, the authors reported a correct diagnosis of 86% and an overall diagnostic accuracy for the detection of malignancy of 92.9% without a pathologist present for the endoscopy 14. A recent study by Kim et al6 reported that the yield of histologic core sample and diagnostic sufficiency rate of EUS-FNB was higher than that of EUS-FNA for histopathological diagnosis of SET of the GI tract in the absence of an onsite pathologist. In the current issue of Clinical Endoscopy, Keswani et al15 reported their retrospective study comparing the diagnostic accuracy of EUS-FNB alone to a conventional sampling method of EUS-FNA with rapid on-site cytology evaluation (ROSE) followed by EUS-FNB in nonpancreatic adenocarcinoma lesions.…”
mentioning
confidence: 99%
“…The sensitivity of EUS-guided tissue acquisition decreases by 10% to 15%, the number of needle passes increases, and the overall procedure time is prolonged in the absence of an on-site pathologist 3,4. Second, for some GI tumors, including GI stromal tumors, cytology yield is limited, and core tissue is sometimes requested by cytopathologists to identify cellular arrangement and tissue architecture for adequate diagnosis and subtyping 5,6. These limitations lead to the need for large needles capable of obtaining core tissue.…”
mentioning
confidence: 99%